2022
DOI: 10.1101/2022.11.10.516016
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Latch Verified Bulk-RNA Seq toolkit: a cloud-based suite of workflows for bulk RNA-seq quality control, analysis, and functional enrichment

Abstract: Background Analysis of high-throughput bulk RNA-sequencing (RNA-seq) data reveals changes in gene expression between diverse conditions. Many tools have emerged to quality control RNA-seq reads, quantify expression levels, conduct functional enrichment among differentially expressed genes, or identify differential RNA splicing. However, unified toolkits for conducting these analyses are lacking. Moreover, existing software does not use cloud-based platforms that provide the necessary storage and computational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…To address biological and methodological variations within a user-friendly framework, an expanding array of open-access semiautomated pipelines is emerging online. Examples include iDEP [18], LVBRS [19], RNAseqChef [20], and NormSeq [21]. It has been observed that achieving consensus among pipelines enhances the diagnostic accuracy of differentially expressed genes (DEGs), suggesting that combining diverse methodologies can yield more robust results [22].…”
Section: Introductionmentioning
confidence: 99%
“…To address biological and methodological variations within a user-friendly framework, an expanding array of open-access semiautomated pipelines is emerging online. Examples include iDEP [18], LVBRS [19], RNAseqChef [20], and NormSeq [21]. It has been observed that achieving consensus among pipelines enhances the diagnostic accuracy of differentially expressed genes (DEGs), suggesting that combining diverse methodologies can yield more robust results [22].…”
Section: Introductionmentioning
confidence: 99%